2022
DOI: 10.1021/jacs.1c13333
|View full text |Cite
|
Sign up to set email alerts
|

Taming the Chlorine Radical: Enforcing Steric Control over Chlorine-Radical-Mediated C–H Activation

Abstract: Chlorine radicals readily activate C–H bonds, but the high reactivity of these intermediates precludes their use in regioselective C–H functionalization reactions. We demonstrate that the secondary coordination sphere of a metal complex can confine photoeliminated chlorine radicals and afford steric control over their reactivity. Specifically, a series of iron­(III) chloride pyridinediimine complexes exhibit activity for photochemical C­(sp3)–H chlorination and bromination with selectivity for primary and seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
81
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(86 citation statements)
references
References 65 publications
3
81
0
1
Order By: Relevance
“…As a matter of fact, while bromine atoms somehow allow for discrete levels of site-selectivity due to the lower BDE of the HÀ Br bond (see Table 1), a HÀ Cl bond is much stronger, providing a considerably higher thermodynamic force for hydrogen abstraction. [114] Furthermore, the greater selectivity of brominemediated HAT can be explained based on the fact that this is an endergonic process. Thus, according to the Hammond postulate, the reaction features a "late" transition state with a marked radical character on the carbon atom.…”
Section: Steering Site-selectivity Of Halogen Radical-mediated Hydrog...mentioning
confidence: 99%
See 1 more Smart Citation
“…As a matter of fact, while bromine atoms somehow allow for discrete levels of site-selectivity due to the lower BDE of the HÀ Br bond (see Table 1), a HÀ Cl bond is much stronger, providing a considerably higher thermodynamic force for hydrogen abstraction. [114] Furthermore, the greater selectivity of brominemediated HAT can be explained based on the fact that this is an endergonic process. Thus, according to the Hammond postulate, the reaction features a "late" transition state with a marked radical character on the carbon atom.…”
Section: Steering Site-selectivity Of Halogen Radical-mediated Hydrog...mentioning
confidence: 99%
“…More recently, Nocera and colleagues managed to go towards the opposite direction and shift the selectivity away from more thermodynamically accessible tertiary positions by capitalizing on steric hindrance (Scheme 27D). [114] In detail, they demonstrated that Cl * , photoeliminated from an Fe III chloride pyridinediimine (PDI) complex via LMCT, can be confined by the secondary coordination sphere of the metal complex itself. This interaction creates a bulky Cl * j arene complex that possesses a considerable steric hindrance compared to the free chlorine atom.…”
Section: Steering Site-selectivity Of Halogen Radical-mediated Hydrog...mentioning
confidence: 99%
“…The chlorine radical-induced charge-transfer complexes were known to alter the selectivity in alkane activation. 21 Based on this strategy, Nocera and co-workers designed an iron(III) pyridinediimine (PDI) complex, 22 of which the ligand could form a charge-transfer complex with a chlorine radical. The arene−Cl• interaction could be leveraged to confine a photoeliminated chlorine radical within the secondary coordination sphere of the synthesized metal complexes, affording steric-controlled products over the reactivity of chlorine radical.…”
Section: Scheme 9 Iron-catalyzed Nitrene Transfer Reactionmentioning
confidence: 99%
“…Although C-H activation reactions have found high utility in synthetic chemistry, site selectivity can be challenging to achieve as the weakest or most sterically-accessible C-H bond is typically activated by the catalyst, it can be difficult to prevent undesired activation of C-H bonds of similar strength, and functional group compatibility can be low. To address these challenges, chemical catalysts have been designed to use ligand architecture or spatial orientation to achieve selectivity [15][16][17][18][19][20][21][22][23] . In contrast, enzymes routinely achieve both stereo-and regioselectivity when presented with similar sites of equivalent reactivity since their three-dimensional chiral architecture naturally creates asymmetry.…”
Section: Main Text Introductionmentioning
confidence: 99%